Dinâmica das forças no fresamento do Inconel 718 utilizando fresa de topo com passo diferenciado - Cosenza, Matheus Coelho (2019)
Vibration stands out as one of the biggest barriers in machining productivity and quality as it results in poor surface finish and dimensional accuracy, increases tool wear and may cause tool fracture and damage to the machine tool itself. In addition, machining heat resistance materials with low machinability, such as Inconel 718, hampers the process efficiency and requires lower cutting parameters. As is well known, the heat generated in the cutting area during machining also has major consequences on the workpiece surface integrity and cutting edge life. So, the Inconel 718 rapid hardening and its low thermal conductivity result in high cutting forces and tools’ cutting performance reduction. Thus, several methods and solutions have been studied to predict and avoid this harmful situation in end milling, such as tools with special geometries, with a variable angular distribution of the cutting edges around the axis of rotation, which is called differential pitch. The present work studies the cutting dynamics comparing the usage of regular tool and variable pitch cutter in machining Inconel 718. Preliminary tests were made on an aluminum part to compare its results with previous work and to determine the experimental strategy to machine the material with lower machinability, Inconel. During the preliminary and final experiments, the cutting forces were measured during the cutting process following an analysis of the experimental data frequencies. The surface integrity of the machined parts were also evaluated and compared. The experimental results confirm the average machining force reduction when using variable pitch tools to machine Inconel 718 and also demonstrate an improvement in the surface’s roughness and ripple. The dynamic analysis shows the reduction of the signals’ amplitude in the harmonics of the rotation frequency of the non-constant pitch tool as well.